Pembelajaran Seni Tari melalui Aplikasi Microsoft Office Team 365 Pada Siswa MAN 2 Tangerang - Purba, Kiki Amelia; Permanasari, Alis Triena; Lestari, Dwi Junianti (Pendidikan Seni Pertunjukan Fakultas Keguruan dan Ilmu Pendidikan Universitas Sultan Ageng, 2023)
ABSTRACK One way to support dance learning in the current situation is through the Microsoft Office Team 365 application as an application technology-based learning medium. This study aims to describe the process and results as well as the supporting and inhibiting factors of learning the art of dance through the Microsoft Office Team 365 application for students at MAN 2 Tangerang. This research uses qualitative research with descriptive method. The results of this study are dance learning can be carried out well and is conveyed even though it is a short lesson. Students can understand the lessons uploaded to Microsoft Office Team 365. Student responses are seen from the collection of group assignments and dancing practices and conducting discussion activities in the comments column on the Microsoft Office Team 365 feature in the application. Keywords: Dance Learning, Microsoft Office Team 365.